The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ajmg.a.33308
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of trisomy 15pter‐q21.2 due to a de novo marker chromosome

Abstract: Supernumerary marker chromosomes (sSMC) may or may not be associated with an abnormal phenotype, depending on the presence of euchromatin, on their chromosomal origin and whether they are inherited. Over 80% of sSMCs are derived from acrocentric chromosomes and half of them include the short arm of chromosome 15. Generally, they appear as bisatellited isodicentric marker chromosomes, most of them are symmetric. These chromosomes are normally originated de novo and are associated with mild to severe intellectua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…The origins of sSMCs in our survey were derived from acrocentric chromosomes (42%), followed by nonacrocentric chromosomes (37%) and the Y chromosome (21%), which is in agreement with the literature [10]. It is reported that chromosome 15 was the most common origin for sSMCs in acrocentric chromosomes, accounting for~30-50% [11]. Chromosome 15-derived sSMCs incorporating the PWACR are associated with developmental delay, mental retardation, ataxia, seizures and behavioural problems and patients with more copies of this region may develop a more severe phenotype [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The origins of sSMCs in our survey were derived from acrocentric chromosomes (42%), followed by nonacrocentric chromosomes (37%) and the Y chromosome (21%), which is in agreement with the literature [10]. It is reported that chromosome 15 was the most common origin for sSMCs in acrocentric chromosomes, accounting for~30-50% [11]. Chromosome 15-derived sSMCs incorporating the PWACR are associated with developmental delay, mental retardation, ataxia, seizures and behavioural problems and patients with more copies of this region may develop a more severe phenotype [12].…”
Section: Discussionsupporting
confidence: 90%
“…Patients excluding the DSCR present mild and nonspecific phenotypes, such as joint hyperlaxity, hypotonia and brachycephaly hypertelorism, epicanthic folds, strabismus and mildly dysmorphic ears [26]. The mother of case 9 without any abnormal clinical phenotype was also a carrier of an sSMC with a mosaic karyotype of 47,XX, +mar [11]/46,XX[39], which is a triploid gain for the same region of 21q11.2q21.1 but with a different morphology, suggesting that the sSMC underwent recombined duplication during through two generations. If the additional euchromatic material is one small copy near the centromere, it can be tolerated.…”
Section: Discussionmentioning
confidence: 98%
“…Such abnormalities may arise due to the generation of gametes containing duplicated or deleted chromosome fragments, which may produce individuals with partial trisomies or monosomies [5]. In the present case, we observed a complex marker chromosome formed by a 3:1 segregation, with tertiary trisomy originated from a maternal reciprocal translocation (15;16).…”
Section: Discussionmentioning
confidence: 49%
“…The rearrangement includes one of the most common regions susceptible to imprinting, the PWS and AS critical region. The methylation status of this critical region was investigated by SNURF–SNRPN exon 1 methylation analysis after PCR amplification of bisulfite‐modified DNA [Zeschnigk et al, 1997; Pacanaro et al, 2010] observed on a 2% agarose gel. PCR primers are specific for the maternal and the paternal allele, generating bands with different molecular weight (313 bp for maternal and 221 bp for paternal alleles).…”
Section: Methodsmentioning
confidence: 99%